The relationship between physical fitness and academic achievement among adolescent in South Korea - Han, Gun-Soo (J Phys Ther Sci, 2018)
[Purpose] The purpose of this study was to identify the relationship between physical fitness level and academic achievement in middle school students. [Subjects and Methods] A total of 236 students aged 13–15 from three middle schools in D city, South Korea, were selected using a random sampling method. Academic achievement was measured by students’ 2014 fall-semester final exam scores and the level of physical fitness was determined according to the PAPS (Physical Activity Promotion System) score administrated by the Korean Ministry of Education. A Pearson correlation test with SPSS 20.0 was employed. [Results] The Pearson correlation test revealed a significant correlation between physical fitness and academic achievement. Specifically, students with higher levels of physical fitness tend to have higher academic performance. In addition, final exam scores of core subjects (e.g., English, mathematics, and science) were significantly related to the PAPS score. [Conclusion] Results of this study can be used to develop more effective physical education curricula. In addition, the data can also be applied to recreation and sport programs for other populations (e.g., children and adult) as well as existing national physical fitness data in various countries.